Investigation of a Progressive Relaxation Training Intervention on Precompetition Anxiety and Sports Performance Among Collegiate Student Athletes - Liang, Dongmei; Chen, Shuqing; Zhang, Wenting; Xu, Kai; Li, Yuting; Li, Donghao; Cheng, Huiying; Xiao, Junwei; Wan, Liyi; Liu, Chengyi (Frontiers in Psychology, 2021)
This study aims to investigate whether simple and convenient Progressive Relaxation Training (PRT) is effective in enhancing collegiate student athletes’ mental health and sports performance. An experimental group of fourteen (six female) and a control group of ten (five female) collegiate student athletes were recruited from among track and field athletes who were preparing for provincial competition. The experimental group was exposed to a PRT intervention in thirty-minute sessions conducted twice per week for a duration of one month. At baseline, the Competitive State Anxiety Inventory-2 (CSAI-2), State-Trait Anxiety Inventory (STAI) and Eysenck Personality Questionnaire-Revised, Short Scale for Chinese (EPQ-RSC) were completed, while only the CSAI-2 was re-assessed at one, two and three weeks after initiation of the intervention. Additionally, within half a day after completing all one’s individual competition events, the CSAI-2 was again assessed in the two groups recalling their memory of their pre-competition state anxiety. Then, the differences in the three dimensions of the CSAI-2 between the two groups at the five time points introduced above were compared. This study also explored whether PRT affected sports performance, defined by the athletes reaching their best records or not, by logistic regressive analysis. This study found significant between-group differences in the self-confidence dimension score at the second and third time points. Through logistic regression analysis, a positive effect of PRT was found for the enhancement of sports performance. In sum, PRT showed positive effects on pre-competition state self-confidence and enhanced sports performance among collegiate student athletes.